Assessing guidelines for burn referrals in a resource-constrained setting: Demographic and clinical factors associated with inter-facility transfer. Issue 5 (August 2017) - Klingberg, A.; Wallis, L.; Rode, H.; Stenberg, T.; Laflamme, L.; Hasselberg, M.
Highlights: Most children fulfilled the referral guidelines for burns. Three out of four children were referred to the burns unit for further management. Many children were not referred despite fulfilling the criteria for referral. Abstract: Aim: The aim was to assess demographic and clinical factors associated with inter-facility referrals for patients with burns in a resource-constrained setting. Methods: This was a cross-sectional case review of patients presenting with a burn at the trauma unit at the Red Cross War Memorial Children's Hospital (RXH) in Cape Town, South Africa. Results: Six hundred and eleven—(71%) children were referred to the burns or the intensive care unit and 253 children were treated and discharged from the trauma unit. Of those admitted as inpatients 94% fulfilled at least one of the criteria for referral and 80% of those treated and discharged fulfilled the criteria for referral. Conclusions: Almost three out of four children evaluated at the trauma unit were referred to the burns unit for further management. However, a large number of patients were treated and discharged from the trauma unit despite being eligible for referral.